Study of Phytochemical screening,Total Phenolic and Flavonoid Content and Antioxidant Activity of Pulicaria glutinosa growing in Saudi Arabia - Jehan Yahya Al-humaidi (International Journal of Phytomedicine, 2016)
Phytochemical screening of P. glutinosa extracts revealed the presence of alkaloids, terpenes, sponins, flavonids, anthraquinone and glycosides. Quantitative determination of total phenolics, total flavonoids, and various in vitro antioxidant activities (DPPH, ABTS metal chelation effect in the Fe2+-ferrozin test system) of the various extracts from the P. glutinosa was carried out. Phenol and flavonoid content of the extract were measured by folin ciocalteu and AlCl3 assays. The Phenol and flavonoid content of the extracts varied between 18.33 – 199.44 mg/g and 14.64 – 164.73 mg/g, respectively. The results showed that the butanol extract of P. glutinosa, which contain highest amount of phenol and flavonoid compounds, exhibited the greatest antioxidant activity in scavenging of DPPH free radical and ABTS radical cation assays. In other hands, results showed that aq. Methanol, butanol and water extracts studied are in metal-chelating assay lower active than EDTA and higher than ascorbic acid as a synthetic antioxidant.